An unmanned surface vehicle for acoustic telemetry surveys of coastal fishes: range testing, real world performance, and comparison with a stationary tracking array - Reyier, Eric; Iafrate, Joseph; Ahr, Bonnie; Watwood, Stephanie; Scheidt, Douglas; Levenson, Jacob; Schumann, Chris (Frontiers in Marine Science, 2025)
Ocean gliders equipped with acoustic telemetry receivers offer a promising approach for studying the movement of marine fishes, yet most surveys to date have been brief and rarely include direct comparisons with traditional stationary tracking methods. To evaluate glider-based tracking, a Wave Glider unmanned surface vehicle (USV) was deployed on eight multi-week missions over the east Florida continental shelf. The survey aimed to systematically detect acoustically tagged animals and compare glider performance to a contemporaneous stationary tracking array, with range tests conducted using two receiver types mounted on the glider. Across 190 days and 9,600 km of survey effort, the Wave Glider recorded 331 animal encounters representing 20 species, with blacktip shark (Carcharhinus limbatus), blacknose shark (C. acronotus), and red drum (Sciaenops ocellatus) among the most frequently detected. Detection range trials yielded 50% detection probabilities at distances up to 350 m. Boosted regression tree models indicated that distance between tag and receiver explained 57–71% of the variance in detection probability, with ocean currents, wave height, and solar irradiance also contributing. Compared to a 62-receiver stationary array, the Wave Glider detected, on average, 64% of the species and 40% of the tagged animals, but less than 2% of the detections over identical timeframes. Further, animal encounters with the glider lasted only 14 minutes on average, versus 48 minutes for stationary receivers. Nonetheless, the glider performed comparably on a per-receiver basis, yielding similar numbers of encounters, animals, and species. Moreover, the Wave Glider successfully navigated complex bathymetry surrounding offshore sand shoals, relocated several shed tags, and paired encounters with a variety of oceanographic and meteorological measurements. These results confirm that USVs are suitable for systematic coastal fish tracking. While single gliders cannot replace stationary arrays in most situations, they are realistic solutions for relocating animals in remote locations, monitoring dispersal across discrete habitat patches (e.g., reefs, wind turbines), and providing highly localized habitat context.